Brown Spot and Narrow Brown Spot Paddy Disease Detection using Color Slicing Method - Md Taujuddin, Nik Shahidah Afifi; I. S Samuri; R. Ibrahim; S. Sari; A. R. A Ghani; Munirah Ab. Rahman (Evolution in Electrical and Electronic Engineering, 2021)
In this research, the main objective is to develop a system to detect the paddy leaves disease which are Brown Spot Disease (BS) and Narrow Brown Spot Disease (NBS). This paper focuses on the image processing techniques to enhance the quality of the images and the color slicing technique to classify the type of paddy leaves disease in the early stage of paddy plantation to avoid the production of low quality of rice. Detection in early stage of paddy plantation is important to ensure a high quality of paddy plant. The methodology involves image acquisition, pre-processing, segmentation and analysis of the paddy leaves disease. All paddy samples will be going through the RBG calculation before going through the color slicing for the paddy disease classification. A total 50 sample paddy leaves images were used and the accuracy is analysed. The accuracy of disease detection for this project is 88%.